2007
DOI: 10.3138/cpp.33.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Just How Much Bigger Is Government in Canada? A Comparative Analysis of the Size and Structure of the Public Sectors in Canada and the United States, 1929–2004

Abstract: We compare the size and structure of the public sectors of Canada and the United States from 1929 to 2004 using national accounting and employment data. The challenge of defining the public sector for comparative purposes is explored and illustrated, especially with respect to the treatment of non-profits, and a number of intriguing similarities and differences in the comparative evolution of the public sectors are identified that remain to be explained. Use of a new Fisher-type government deflator for Canada … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In Canada, Imbeau et al (2001), examining the period from 1971 to 1995, found ''quite modest'' (48) growth in real government size in seven provinces and no growth in the remaining three. Ferris and Winer (2007) found that after controlling for the faster growth of government prices relative to private-sector prices, the real size of federal government actually declined marginally from 1961 to 2003, in both Canada and the United States. In short, much of government growth is a product of price growth rather than new or expanded service provision.…”
mentioning
confidence: 94%
“…In Canada, Imbeau et al (2001), examining the period from 1971 to 1995, found ''quite modest'' (48) growth in real government size in seven provinces and no growth in the remaining three. Ferris and Winer (2007) found that after controlling for the faster growth of government prices relative to private-sector prices, the real size of federal government actually declined marginally from 1961 to 2003, in both Canada and the United States. In short, much of government growth is a product of price growth rather than new or expanded service provision.…”
mentioning
confidence: 94%